A COMPARISON BETWEEN MEDICAL AND NON-MEDICAL STUDENTS IN INDIA FOR CADAVERIC ORGAN DONATION (COD): A QUESTIONNAIRE BASED STUDY (Journal of Forensic Medicine & Toxicology, 2016)
Background: The larger number of people in our country are in waiting list for organ transplantation (OT) which could be overcome by organ donation (OD). Our aim of the study was to evaluate the awareness regarding organ donation after and before death. Material and Methods: An observational study was conducted among medical students (SMART group), non medical students (VIPgroup) and paramedics (VVIP group) and Staff (Tension group) in our Institute population. Total 430 participants were answered through questionnaire based providing information about the knowledge and attitude towards organ donation. Results: 96.33% of entire study group had strongly positive attitude about cadaveric organ donation from the medical student (SMART group), Non Medical student (VIPgroup) 30 % had no idea about this. Paramedics (VVIPgroup) 58% of total participants were unwilling for organ donation after death. Staff (Tension group) 75% of total participants were unwilling for organ donation after death. Discussion: The present study has been done elaborately to find out the different barriers for organ donation. It is clear from the study that though there is high level of awareness, nobody has filled up the pledge form till now. It indicates that there is a gap between the knowledge and motivation for organ donation after death which has to be overcome by proper guidance and education. Media and other voluntary organizations could take an important role for this purpose. Conclusion: The present study has been done elaborately to find out the different barriers for cadaveric organ donation (COD) among students been identified.
Keywords: Awareness; Cadaver; Medical and nonmedical population